Novel treatment modalities for nonalcoholic steatohepatitis - Satapathy, Sanjaya K.; Sanyal, Arun J (Trends in endocrinology and metabolism, 2010)
Nonalcoholic steatohepatitis (NASH) is the most common cause of chronic liver disease in the Western world. It can lead to cirrhosis and hepatocellular cancer, and is independently associated with an increased risk of death due to cardiovascular and liver diseases. Over the past 5 years, numerous advances in understanding its pathogenesis have been made, providing a rationale for translation of this information into clinical trials. Although the optimum therapy is still awaited, there is strong evidence to support the use of vitamin E in selected subjects. Many other potential therapeutic options are now available. In this paper, we review the status of both current and emerging therapeutic strategies for patients with NASH.